1991
DOI: 10.1093/ajh/4.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Blood Pressure Response to Excercise in Borderline Hypertension: A Two Year Follow-up Study

Abstract: Twenty-eight men with borderline hypertension according to the World Health Organization criteria underwent maximal exercise testing, and then were followed for a two year period. The prevalence of abnormal blood pressure behavior during exercise was 53.58% (n = 15). During follow-up established hypertension developed in 63.33% (n = 10) of subjects with an abnormal blood pressure response to exercise, and only in 15% (n = 2) of subjects with normal blood pressure behavior. In predicting established hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Both isometric (Parker et al, 1987;Chaney & Eyman, 1988;Matthews et al, 1993) and dynamic (Dlin et al, 1983;Chaney & Eyman, 1988;Wilson et al, 1990;Guerrera et al, 1991;Manolio et al, 1994;Allison et al, 1999;Singh et al, 1999;Miyai et al, 2000) exercise tests have also in the previous studies signi®cantly predicted BP trends and target-organ damage. Both isometric (Parker et al, 1987;Chaney & Eyman, 1988;Matthews et al, 1993) and dynamic (Dlin et al, 1983;Chaney & Eyman, 1988;Wilson et al, 1990;Guerrera et al, 1991;Manolio et al, 1994;Allison et al, 1999;Singh et al, 1999;Miyai et al, 2000) exercise tests have also in the previous studies signi®cantly predicted BP trends and target-organ damage.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Both isometric (Parker et al, 1987;Chaney & Eyman, 1988;Matthews et al, 1993) and dynamic (Dlin et al, 1983;Chaney & Eyman, 1988;Wilson et al, 1990;Guerrera et al, 1991;Manolio et al, 1994;Allison et al, 1999;Singh et al, 1999;Miyai et al, 2000) exercise tests have also in the previous studies signi®cantly predicted BP trends and target-organ damage. Both isometric (Parker et al, 1987;Chaney & Eyman, 1988;Matthews et al, 1993) and dynamic (Dlin et al, 1983;Chaney & Eyman, 1988;Wilson et al, 1990;Guerrera et al, 1991;Manolio et al, 1994;Allison et al, 1999;Singh et al, 1999;Miyai et al, 2000) exercise tests have also in the previous studies signi®cantly predicted BP trends and target-organ damage.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to BPs in the postural tests, some of the BPs at the exercise tests in the present study were more predictive than the casual BP measurements alone. Both isometric (Parker et al, 1987;Chaney & Eyman, 1988;Matthews et al, 1993) and dynamic (Dlin et al, 1983;Chaney & Eyman, 1988;Wilson et al, 1990;Guerrera et al, 1991;Manolio et al, 1994;Allison et al, 1999;Singh et al, 1999;Miyai et al, 2000) exercise tests have also in the previous studies signi®cantly predicted BP trends and target-organ damage. In contrast to previous studies using only few tests, this follow-up allows the comparison of both isometric and dynamic exercise tests to postural tests as predictors in the same study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Studies have suggested that an exaggerated blood pressure response to maximal exercise may be useful in detecting individuals who are prone to developing hypertension in late years. Guerrera et al [1] found in a 2-year follow-up that maximal exercise testing had a sensitivity of 83.33%, specificity of 68.75%, positive predictive value of 66.66% and a negative pedictive value of 84.61% in predicting established hypertension development. In the same way, Fagard et al [2] suggested that intra-arterial pressures at rest and during submaximal and peak exercise significantly predict mortality and the incidence of cardiovascular events in hypertensive men.…”
mentioning
confidence: 99%